2006
DOI: 10.1159/000094375
|View full text |Cite
|
Sign up to set email alerts
|

Immunolesions of Glucoresponsive Projections to the Arcuate Nucleus Alter Glucoprivic-Induced Alterations in Food Intake, Luteinizing Hormone Secretion, and GALP mRNA, but Not Sex Behavior in Adult Male Rats

Abstract: Metabolic signals such as insulin, leptin and glucose are known to alter hypothalamic function. Although insulin and leptin are known to directly alter hypothalamic areas that regulate reproduction, the mechanisms by which glucose alters reproductive function are not as clear. Catecholaminergic neurons in the A1/C1 region in the hindbrain are glucose-responsive and project to the arcuate nucleus. To determine if this pathway is involved in the regulation of sex behavior and luteinizing hormone (LH) secretion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 85 publications
(60 reference statements)
1
24
0
Order By: Relevance
“…Alternatively, the time course of GALP appearance in the Arc is similar to that reported by others for hindbrain catecholaminergic innervation of the ventromedial hypothalamus [39,40]. A recent report demonstrated that GALP gene expression is also regulated by catecholaminergic afferents from the hindbrain [30]. It is possible that GALP gene expression is initially triggered by the appearance of hindbrain catecholaminergic neurons in the hypothalamus.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Alternatively, the time course of GALP appearance in the Arc is similar to that reported by others for hindbrain catecholaminergic innervation of the ventromedial hypothalamus [39,40]. A recent report demonstrated that GALP gene expression is also regulated by catecholaminergic afferents from the hindbrain [30]. It is possible that GALP gene expression is initially triggered by the appearance of hindbrain catecholaminergic neurons in the hypothalamus.…”
Section: Discussionsupporting
confidence: 84%
“…In adult rats, GALP is expressed in the Arc of the hypothalamus and GALP gene expression is regulated by leptin, insulin, and metabolic fuels [6,30,31]. Our study has shown that in neonatal rats, GALP gene expression does not appear until late postnatally (~PND12).…”
Section: Discussionmentioning
confidence: 62%
“…46 These findings suggest that GALP mRNA in the pituicytes is controlled by thyroid hormone, and that GALP mRNA is physiologically associated with the activation of oxytocin-and vasopressin-secreting neurons during lactation. 46 Catecholaminergic neurons in the A1/C1 region in the medulla oblongata are glucose responsive and project to the ARC, 47 and A1/C1 efferents to the hypothalamus are involved in the glucostatic regulation of GALP mRNA, feeding behavior and LH secretion. 47 …”
Section: Regulation Of Galp Neuronsmentioning
confidence: 99%
“…46 Catecholaminergic neurons in the A1/C1 region in the medulla oblongata are glucose responsive and project to the ARC, 47 and A1/C1 efferents to the hypothalamus are involved in the glucostatic regulation of GALP mRNA, feeding behavior and LH secretion. 47 …”
Section: Regulation Of Galp Neuronsmentioning
confidence: 99%
See 1 more Smart Citation